The Role of Cation-Vacancies for the Electronic and Optical Properties of Aluminosilicate Imogolite Nanotubes: A Non-local, Linear-Response TDDFT Study - Poli, Emiliano; Elliott, Joshua D.; Chulkov, Sergey K.; Watkins, Matthew B.; Teobaldi, Gilberto (Frontiers in Chemistry, 2019)
We report a combined non-local (PBE-TC-LRC) Density Functional Theory (DFT) and linear-response time-dependent DFT (LR-TDDFT) study of the structural, electronic and optical properties of the cation-vacancy based defects in aluminosilicate (AlSi) imogolite nanotubes (Imo-NTs) that have been recently proposed on the basis of Nuclear Magnetic Resonance (NMR) experiments. Following numerical determination of the smallest AlSi Imo-NT model capable of accommodating the defect-induced relaxation with negligible finite-size errors, we analyse the defect-induced structural deformations in the NTs and ensuing changes in the NTs’ electronic structure. The NMR-derived defects are found to introduce both shallow and deep occupied states in the pristine NTs’ band gap (BG). These BG states are found to be highly localised at the defect site. No empty defect-state is modelled for any of the considered systems. LR-TDDFT simulation of the defects reveal increased low-energy optical absorbance for all (but one) defects, with the appearance of optically active excitations at energies lower than for the defect-free NT. These results enable interpretation of the low-energy tail in the experimental UV-vis spectra for AlSi NTs as being due to the defects. Finally, the PBE-TC-LRC-approximated exciton binding energy for the defects’ optical transitions is found to be substantially lower (up to 0.8 eV) than for the pristine defect-free NT’s excitations (1.1 eV).